Population Status and Threats of Phaedyma Aspasia kathmandia Fujioka 1970 (Lepidoptera: Nymphalidae), an Endemic Subspecies of Butterfly in Godavari Forest of Central Nepal - Khanal, Bhaiya; Chalise, Mukesh Kumar; Solanki, Ghana Shyam (Journal of Natural History Museum, 2015)
This study was designed specifically to assess the population status and prevailing threats of Phaedyma aspasia kathmandia an endangered and endemic subspecies of butterfly confined to a very narrow range at 1600–1800 m of elevation in Godavari forest of Lalitpur district of central Nepal. This study revealed the occurrence of only 11 individuals of this species during the study period on July, 2011 and May to July, 2012.The underlying threat to this butterfly is the establishment of the marble quarry around its habitat area. Habitat shrinkage of this butterfly has been noticed due to construction of road at the expense of pristine forest of this part. J. Nat. Hist. Mus. Vol. 27, 2013: 87-91